STATE RESPONSIBILITY FOR HUMAN RIGHT VIOLATIONS IN CASES OF TRANSBOUNDARY ENVIRONMENTAL HARM: A NEW CONCEPT OF EXTRATERRITORIALITY REGARDING THE APPLICATION OF INTERNATIONAL HUMAN RIGHTS TREATIES? - Cuckovic, Bojana (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
In an advisory opinion on human rights and environment delivered in late 2017, the Inter-American Court of Human Rights addressed the question of whether a State party to the American Convention on Human Rights may be responsible for violations of human rights of persons outside its territory by reason of the environmentally harmful activities with transboundary effects undertaken in the territory of that State, in case the State had effective control over those activities. The paper offers an in-depth analysis of IACtHR’s positive answer to this question and compares it to the threshold for extraterritorial jurisdiction that has so far mainly been interpreted rather restrictively by the European Court of Human Rights. The author, inter alia, concludes that the position taken by the IACtHR essentially redefines the traditional effective control over territory or persons test in a number of aspects. These new elements are qualified as three-fold – substantial, content-related and spatial. The nature of the new concept is, in addition, the subject-matter of the analysis. The paper researches upon whether the extensive extraterritoriality threshold can be considered as a general human rights standard, or whether it rather represents a (mis)interpretation of the duty to prevent transboundary environmental harm as a well established rule of international environmental law? After offering valid arguments both in favour and against each of the two propositions, the author constructs a compromise solution based on certain elements of both approaches as the most acceptable position. Finally, prospects for further expanding the extensive extraterritoriality threshold to other areas and other human rights systems are also discussed.
Keywords: extraterritorial jurisdiction; transboundary environmental harm; human rights; effective control; Inter-American Court of Human Rights; European Court of Human Rights